Obesity intervention outcome: i)the effect of pharmacological intervention in failed lifestyle intervention ii)weight loss maintenance with cessation of pharmacological intervention - Aida Hanum, Ghulam Rasool (Pusat Pengajian Sains Perubatan, 2013)
This study aimed to determine the effect of anti-obesity drug treatment in overweight and obese subjects who had failed to achieve satisfactory weight loss after a 9 months' weight loss intervention programme involving education on lifestyle modification. 25 subjects had originally undergone a 9 months' intervention programme aimed to reduce weight involving education on lifestyle modification. 11 (8 females and 3 males) subjects who had failed to reduce their weight satisfactorily (defined as still having body mass index (BMI) 2: 27 kg/m2 after intervention) were offered anti-obesity drugs for a period of 4 months. Anthropometric measurements, body composition (body and visceral fat percentages), metabolic and cardiovascular (CVS) profiles were measured at 9 months after completing lifestyle modification, and repeated at the end of 4 months with anti-obesity drugs. Anti-obesity drugs used in this study were orlistat 120 mg three times daily or sibutramine 10- 15 mg daily. subjects were on orlistat while 4 were on sibutrarnine. These 11 subjects did not significantly reduce weight when they were on 9 months education on lifestyle modification, mean weight before and after intervention was 75.7 (18.8) vs 76.5 (21.0) kg; p=0.452. Weight reduced significantly after 4 months drug treatment by 2.06 kg (p=0.041). Visceral fat significantly reduced from 13.7 (6.5)% to 12.9 (6.9)% (p=0.036) after drug treatment. A borderline reduction in waist circumference was seen (87.2 (10.2) em vs 85.9 (11.0) em, (p = 0.073). No difference was seen in lipid profile, fasting blood sugar, insulin level and resistance, blood pressure and arterial stiffuess with 4 months anti-obesity agents. Or!istat and Sibutramine reduced weight significantly in subjects who had failed to reduce weight with education on lifestyle medication. The weight reduction was however modest at 2.7% and was not associated with improvements in other CVS and metabolic risk markers.